IoT Based Intelligent Traffic Management and Violators Recognition System (International Journal of Innovative Research in Computer Science & Technology, 2021)
This paper presents a new system to  manage traffic in a high congested area. The IoT technology  is utilized for traffic management and identification of  defaulters. The raspberry-pi, RFID, and IR sensors are used  to implement the system. The proposed system is  incorporated with decisive and round-robin algorithm to  detect the optimal path to further indicate the direction for  traffic. IR sensors regulates the density of traffic in an area  by RFID. The traffic signals connected with cameras in  metro cities cab be upgrade by connecting to IoT. This  system is very useful during the pandemic. The police can  easily control the traffic from mobile phone from their  home and identify the defaulters also. The proposed system  helps in sequestering of ambulance, firefighting vehicles  from daily traffic. There is an extra benefit of using RFID  that supports in locating the robbed or snatched vehicles.
Keywords: IR Sensor; IoT; RFID; Raspberry-pi